Translation, adaptation, and initial evaluation of a guided self-help intervention to reduce psychological distress among nurses during COVID-19 in China - Tian, Tian; Sun, Jingwen; Jiang, Yue; Guo, Qian; Huang, Zeyu; Wang, Duolao; Rahman, Atif; Li, Xiaomei; Yang, Lei (Frontiers in Psychiatry, 2023)
Background This study aimed to reduce the unprecedented and intense psychological distress that nurses were forced to experience during the COVID-19 pandemic. A Chinese version of the World Health Organization's Self-Help Plus (SH+) intervention guide was adapted and tested among nurses. The objective of this study was to translate and adapt the SH+ guideline into the Chinese version and to test its feasibility in reducing psychological distress among nurses during COVID-19. Methods A staged approach comprising translation, adaptations, initial evaluation by pilot implementation, and a qualitative process evaluation was conducted in two hospitals in Xi'an, China. The translation of the Chinese version was authorized by the World Health Organization. We adapted SH+ for use among clinical nurses working during the pandemic in China through a qualitative process evaluation, which was guided by the descriptive phenomenological study design. The outcomes of the pilot included psychological distress, psychological flexibility, depressive and anxiety symptoms, post-traumatic stress disorder (PTSD) symptoms, and subjective psychological wellbeing, which were assessed using the Kessler 6 symptom checklist, the Comprehensive Assessment of ACT Process (CompACT), the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder scale (GAD-7), the PTSD Checklist-Civilian Version (PCL-C), and the Index of Wellbeing (IWB), respectively. Results The SH+ materials, including audio-recorded sessions and an accompanying illustrated manual, were translated into Chinese and adapted in line with feedback from the nurses. An uncontrolled pilot study (n = 28) for 5 weeks showed a statistically significant reduction of psychological distress (mean difference in Kessler 6 score, −2.74; 95% CI [−3.71, −1.78]; p < 0.001). We also found improvements in psychological flexibility (mean difference in CompACT score, 6.89; 95% CI [−12.35, −4.47]; p < 0.001), subjective psychological wellbeing (mean difference in IWB score, 0.86; 95% CI [0.07, 1.65]; p < 0.05), and depressive symptoms (mean difference in PHQ-9 score, −1.52; 95% CI [−2.78, −0.26]; p < 0.05). The process evaluation showed that nurses found the SH+ program very useful but difficult to adhere to. Conclusion We found that the translated Chinese version of SH+ was applicable and feasible in the Chinese cultural context. There was a potential effect of adapted SH + in reducing nurses' psychological distress during COVID-19 and suggested the value of exploring strategies to increase adherence to the program.